THE INFLUENCE OF SELF ASSESSMENT SYSTEM, TAX AUDIT, TAX COLLECTION ON REVENUE (PPN) AT KPP PRATAMA BANYUWANGI - Putri Choirunnisa Alfandi; Novi Lailiyul Wafiroh (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to examine how tax audits, tax collection, and self-assessment techniques impact Value Added Tax (VAT) revenue at the Banyuwangi Pratama Tax Office (KPP). The State Budget (APBN) is heavily influenced by VAT, which constitutes a significant portion of state revenue. However, optimizing VAT revenue still faces several challenges. These include suboptimal taxpayer compliance, inefficient audits, and suboptimal collection processes. In this context, the self-assessment system, which allows individuals to choose, pay, and record their own tax obligations, plays a strategic role but also requires oversight and legal enforcement support. This study employs a quantitative methodology using secondary data collected from the Banyuwangi Pratama Tax Office between 2021 and 2024. The sampling technique was carried out utilizing the method of purposive sampling, while Panel data regression was used for data analysis with the help of E-Views 12 software. The independent variables in this study include the number of VAT Periodic Tax Returns (as an indicator of the self-assessment system), the number of Tax Assessment Letters (tax audit indicator), and the amount of arrears that were successfully collected (tax collection indicator). The dependent variable is monthly VAT revenue that has been designed in the form of a time series data deflation index. This indicates that the implementation of a tax collection system based on taxpayer awareness must be balanced with strict supervision and consistent law enforcement so that tax revenue can be optimized. The practical implications of these results suggest that the Banyuwangi Pratama Tax Office and the Directorate General of Taxes need to improve the effectiveness of the implementation of self-assessment, audit, and collection in order to secure VAT revenue.